The effect of banking services on the business performance of bank agents in Kenya - K. Gitonga Margaret; N. Kiraka Ruth (Cogent Business & Management, 2019)
Agency banking is a relatively new banking concept introduced in Kenya in 2010 by the Central Bank of Kenya (CBK), the main objective being to increase financial services outreach and promote financial inclusion of the unbanked and under-banked population. The current study, based on agency theory, sought to assess the effect of banking services on the business performance of bank agents in Kenya from an entrepreneurial perspective. A quantitative research survey design was adopted for the study, and questionnaires were used for data collection. A sample of 384 respondents from three constituencies in Nairobi (Roysambu, Kasarani and Kamukunji) participated in the study. Both descriptive and inferential statistics were used to analyse data. Findings revealed that while there was growth in business turnover per month for agents after signing up for agency banking, this was only true for those with a turnover of above Kshs. 150,000. The study recommends that other entrepreneurs should consider being banks agents, while the existing ones should increase their capital to reap the most from agency banking.
Keywords: 650; agency banking; business performance; Kenya; financial inclusion